2014
DOI: 10.1038/hr.2014.72
|View full text |Cite
|
Sign up to set email alerts
|

The milk-derived peptides Val-Pro-Pro and Ile-Pro-Pro attenuate arterial dysfunction in L-NAME-treated rats

Abstract: Both endothelial dysfunction and arterial stiffness are surrogate markers of atherosclerosis and thus cardiovascular (CV) events. The milk-derived peptides Val-Pro-Pro (VPP) and Ile-Pro-Pro (IPP) inhibit angiotensin-converting enzyme, dilate blood vessels ex vivo and stimulate nitric oxide (NO) production in cells. In this study, we investigated the effects of either VPP or IPP on arterial function and on target organ damage in vivo. Male Wistar rats were treated with N(G)-nitro-L-arginine methyl ester hydroch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In fact, the inhibition of this enzyme is the main mechanism implied in the anti-hypertensive effect of dietary peptides [9,10,11]. In addition, endothelial function, which maintains normal vascular tone and blood fluidity to maintain normotensive BP values, has been demonstrated to be the target for some anti-hypertensive peptides [12,13,14]. In HTN, endothelial function is impaired, which presents a decreased presence of vasodilator factors, such as nitric oxide (NO) or prostacyclin (PGI 2 ), and/or increased presence of endothelium-derived contracting factors, such as endothelin 1 (ET-1) [15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the inhibition of this enzyme is the main mechanism implied in the anti-hypertensive effect of dietary peptides [9,10,11]. In addition, endothelial function, which maintains normal vascular tone and blood fluidity to maintain normotensive BP values, has been demonstrated to be the target for some anti-hypertensive peptides [12,13,14]. In HTN, endothelial function is impaired, which presents a decreased presence of vasodilator factors, such as nitric oxide (NO) or prostacyclin (PGI 2 ), and/or increased presence of endothelium-derived contracting factors, such as endothelin 1 (ET-1) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Numbers of BAPs derived from various food proteins (milk, plant, egg, soybean, meat, wheat, rice, potato, corn silk, fish, etc.) have been found to be well suited to treat inflammation or IBD symptoms in vivo ( Table 2 ), such as Ala-Gln (AQ) [ 9 , 52 54 ], DIKTNKPVIF [ 45 ], EWP [ 55 ], GLTSK [ 56 ], glycomacropeptide [ 57 60 ], lunasin [ 15 ], IRW [ 11 , 61 63 ], IQW [ 62 64 ], KGHYAERVG [ 65 ], KPV [ 66 ], PTGADY [ 67 ], QCQCAVEGGL [ 68 ], QEPVL, QEPV [ 6 ], RILSILRHQNLLKELQDLAL [ 69 ], SSEDIKE [ 70 ], TMKLLLVTL [ 43 ], VPP [ 31 , 46 , 71 , 72 ], IPP [ 71 , 72 ], VPY [ 33 ], WH [ 41 ], casein hydrolysates [ 73 ], soybean dipeptides and tripeptides [ 74 ], peptide P-317 [ 75 ], pyroGlu-Leu [ 76 ], β -Casofensin [ 77 ], γ -EC, and γ -EV [ 47 ]. These studies suggest that oral administration of food-derived BAPs have anti-inflammatory effects, and they can be the therapeutic agents for inflammatory-related diseases, including IBD [ 78 ].…”
Section: The In Vivo Studies Of Baps On Inflammmentioning
confidence: 99%
“…Proinflammatory IL-6 and IL-1 β were reduced, and atherosclerosis was attenuated by oral administration of VPP and IPP [ 71 ]. Arterial dysfunction was attenuated by drinking water with VPP and IPP through increasing vasorelaxation and nitrite and nitrate and reducing pulse wave velocity and cardiac and renal damage [ 72 ]. It was reported that VPP attenuated inflammation via the MAPK-JNK pathway by reducing monocytes, macrophages, CD18, IL-6, and MCP-1 in adipose inflammatory mice [ 46 ].…”
Section: The In Vivo Studies Of Baps On Inflammmentioning
confidence: 99%
“…ACE inhibitory peptides with potential antihypertensive properties have been identified from both animal and plant sources [122,123]. VPP and IPP are the well-known casein-derived tripeptides with antihypertensive, vasculo-protective, antioxidant, and anti-inflammatory properties as shown in vivo [124][125][126][127]. The reported effect of these peptides on reducing blood pressure in clinical trials is controversial [128][129][130][131] and needs further investigation.…”
Section: Dairy-derived Peptidesmentioning
confidence: 99%